Stroboscopy while Lifting Weights: A New Assessment Technique for Observing the Larynx in Strength Athletes while Lifting Weights (with and without Valsalva maneuver) - Ebrahimi, Samaneh; Avatef Rostami, Mohsen; Gholami, Mandana; Dickinson, John W; Bakhshi, Mahdi; Ahmadi, Aslan (Health Nexus, 2023)
Lifting weights is a popular exercise method for improving the physical characteristics underlying performance in a wide range of sports. In order to perform these lifts safely and efficiently, strength athletes use purposeful holding of breath, strong exhalation against closed vocal cords. These are commonly known as Valsalva Maneuvers (VM) or hard glottis closures to increase core stability and reduce some of the load on the spine, and to facilitate lifting by increasing glottis closure and subsequently increasing intra-thoracic and intra-abdominal pressure. This function may expose athletes to an increased risk of laryngeal irritation or injury due to excessive pressure on the vocal cords during VM performance. Despite extensive weight training exercises in sports, its effects on vocal cords and overall laryngeal health have not yet been systematically studied. This brief methodological report describes how to safely use sports stroboscopy in strength training with weightlifting. This technique was safe and allowed to receive high quality and stable images of the larynx with minimal impact on weightlifting.